The impact of proficiency and independence of internal audit activity on reducing fraud: Evidence from public organizations in Sulaymaniyah City - Hussein Salih, Rebwar (Iraqi Journal for Administrative Sciences, 2025)
This research aimed to measure the influence of the proficiency and independence of the internal audit activity in reducing fraud via analyzing internal auditor challenges in public institutions in Sulaymaniyah City in north of Iraq. For collecting primary data, the research utilized questionnaire method, the sample of the research comprised of 60 internal auditors in public organizations in Sulaymaniyah City, simple linear regression method was applied to evaluate the of influence of proficiency and independence of the internal audit function in mitigating defraud. The outcome discloses that the proficiency and Independence variables in internal audit operation significantly and positively impacted on minimizing fraud. Hence the study recommends that general managers should prioritize offering adequate training, holding scientific seminars, opening practical courses to the internal auditors with guaranteeing full independence to reduce the risk of fraud.